Penerapan Zahir Accounting Versi 5.1 Pada Distributor Air Galon - Dimas Hogie Sei Naga; Sulistiyah Sulistiyah (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2023)
In today's technological era where technological developments are increasingly sophisticated and fast to make it easier for humans to carry out work with all activities, data can be analyzed for company development. Computers can process all types of data, one of which is accounting data. For companies in the gallon water distributor sector, it is very important that all accounting transactions are recorded using computer technology. For this reason, the author tries to apply the recording of accounting transactions using Zahir Accounting Software Version 5.1. Many companies in the gallon water distributor sector do not record their financial transactions in a computerized manner, which means that the recording of financial transactions is still manual. Recording manually makes it possible for transactions to be inaccurate and requires a lengthy process to analyze financial statements. Application of accounting software using Zahir Accounting Version 5.1 is a solution for all financial transactions recorded in a computerized manner. A computerized system certainly makes all accounting transactions more accurate and more efficient in displaying financial reports.